Comparative evaluation of the efficacy of three different retreatment files in removing root canal filling material: An In vitro confocal microscopy study - Meghna Sarah Abraham; Aravind R. Kudva; Prathap M. S. Nair; Shravan Kini; Samreena Kalander; Faseeh Muhammed Bin Farookh (Endodontology)
Aim: The aim is to compare the cleanability attained by three commercial retreatment file systems in removing residual root canal filling from dentinal tubules using Confocal Laser Scanning Microscopy (CLSM). Methods: Fifty-one single-rooted human premolars were decoronated at a standardized root length of 16 mm, and routine root canal treatment was performed in a crown-down fashion. All samples were obturated using single-cone gutta-percha (GP) combined with sealer, coated with rhodamine. The teeth were then sealed with Cavit-G and allowed 2 weeks to set. Following this, three distinct retreatment file systems were used to retreat all samples (n = 17): Group 1-ProTaper Universal Retreatment (PTUR) files, Group 2- Hyflex Remover files, and Group 3-MTwo Retreatment files. Thereafter, GP coated in sodium fluorescein was used to re-obturate the canals. Samples were sectioned at 2, 4, and 6 mm from the apex and each section examined using CLSM. Results: Hyflex Remover showed significant removal of root canal filling material, as reflected in the mean values of residual filling material percentage (P < 0.05) which were 0.16 ± 0.2, 0.44 ± 0.59, and 0.66 ± 0.46 at 2, 4, and 6 mm, respectively. The highest values were shown by MTwo group, i.e., 0.99 ± 0.52, 2.5 ± 1.09, 2.63 ± 2.01 at progressive levels from apex. Conclusion: Within the limitations of this study, regarding the amount of residual filling materials removed, Hyflex Remover exhibited the highest efficiency, followed by PTUR and MTwo file systems.